IMPLEMENTASI MODEL PEMBELAJARAN TEACHING AT THE RIGHT LEVEL (TARL) BERBANTUAN LEARNING MANAGEMENT SYSTEM (LMS) UNTUK MENINGKATKAN MOTIVASI BELAJAR MAHASISWA PPG CALON GURU - Ni Made Serma Wati; Ni Nyoman Serma Adi (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
The Teaching at the Right Level (TaRL) Learning Model is a teaching approach that focuses on students' learning readiness, not just at the class level. The TaRL approach provides flexibility in teaching according to students' abilities. The purpose of this study was to determine the implementation of the Teaching at the Right Level (TaRL) learning model assisted by LMS can increase the learning motivation of PPG Prospective Teacher students, wave 2, semester 2, 2024/2025 academic year. This type of research is Classroom Action Research. The subjects of this study were 34 PPG Prospective Teacher students, wave 2, semester 2, 2024/2025 academic year at LPTK IKIP Saraswati and the object of the research was learning motivation. This study went through two cycles consisting of four stages of the activity process including (1) planning, (2) action, (3) observation, and (4) evaluation and reflection. Data collection techniques used non-test techniques, observation techniques, and interview techniques. The results of the study indicate that the implementation of the Teaching at the Right Level (TaRL) learning model assisted by LMS can increase the learning motivation of PPG Prospective Teacher students, wave 2, semester 2, 2024/2025 academic year. This statement is proven by the fact that in the pre-cycle the learning motivation was at a percentage of 29.4% with a low category, in cycle I the percentage of learning motivation increased to 50% with a moderate category and in cycle II it increased to 88.3% with a very high category.